Oxaliplatin-Induced Neuropathy: Genetic and Epigenetic Profile to Better Understand How to Ameliorate This Side Effect - Branca, Jacopo Junio Valerio; Carrino, Donatello; Gulisano, Massimo; Ghelardini, Carla; Di Cesare Mannelli, Lorenzo; Pacini, Alessandra (Frontiers in Molecular Biosciences, 2021)
In the last decades, oxaliplatin was used as chemotherapeutic agent for colorectal cancer and other malignancies as well. Oxaliplatin interferes with tumor growth predominantly exerting its action in DNA synthesis inhibition by the formation of DNA-platinum adducts that, in turn, leads to cancer cells death. On the other hand, unfortunately, this interaction leads to a plethora of systemic side effects, including those affecting the peripheral and central nervous system. Oxaliplatin therapy has been associated with acute and chronic neuropathic pain that induced physician to dose reduction or treatment discontinuation. Recently, the capability of oxaliplatin to alter the genetic and epigenetic profiles of the nervous cells has been documented and the understanding of gene expression and transcriptional changes may help to find new putative treatments for neuropathy. The present article is aimed to review the effects of oxaliplatin on genetics and epigenetics mechanism to better understand how to ameliorate neuropathic pain in order to enhance the anti-cancer potential and improve patients’ quality of life.